Socio-ethical Objections to Assisted Suicide - Spieker, Manfred (Chrześcijaństwo-Świat-Polityka, 2024)
Legal considerations regarding suicide are not just a legislative issue, but largely concern the deepest cultural underpinnings of the political community. Recent court rulings, in particular by the German Federal Constitutional Court, reveal far-reaching changes in the understanding of human nature. Under the lofty slogans of human rights and freedom, there is a systematic transformation of the role of law as guarantor of absolute human autonomy. Taking one's own life or assisted suicide is no longer understood as an unethical act, and is increasingly presented in terms of an entitlement or even a duty.